Respostas
respondido por:
3
o resultado é X=7...
viniaS2:
Eu acho
respondido por:
4
x² - 7x = 0
delta=b²-4.a.c a=1 b=7 c=0
delta=49-4.7.0
delta=49-0
x= -b +- raiz de delta / dividido por 2.a
x= -(-7) +- rais de 49 / dividido por 2
x¹= +7 -49 / dividido por 2 = -21
x²= +7 +49 / dividido por 2 = 28
R: s={-21,28}
delta=b²-4.a.c a=1 b=7 c=0
delta=49-4.7.0
delta=49-0
x= -b +- raiz de delta / dividido por 2.a
x= -(-7) +- rais de 49 / dividido por 2
x¹= +7 -49 / dividido por 2 = -21
x²= +7 +49 / dividido por 2 = 28
R: s={-21,28}
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás